Increasing Overall Equipment Effectiveness on 650T Injection Machines with a Lean Manufacturing Approach - Suhendra Suhendra; Tri Ngudi Wiyatno (Jurnal Informasi dan Teknologi, 2024)
At the end of April 2024, national car sales for the domestic market were recorded to have decreased by 34.91% compared to the previous month. This negative trend, of course, disrupts company profits, including PT XYZ as a supplier of automotive components in Indonesia. This decline triggered the company to carry out cost reduction activities in the production area. However, in reality there is still a lot of waste during production, one of which is in the 650T injection molding process. The high cycle time of the injection process resulted in the Overall Equipment Effectiveness (OEE) target not being achieved. The lean manufacturing approach and DMAIC cycle as a research method aims to identify non-value added activities as well as make improvements by reducing the injection process cycle time from 86 to 57 seconds. These improvements made the OEE target for the 650T injection machine achieved because it increased from 67.9% to 76.3%.